Hubungan Tingkat Pengetahuan Ibu Tentang Kebersihan Dengan Perilaku Cuci Tangan Pada Anak Pra Sekolah Di Tk Karangasem Surakarta - Putri, Mukzizatul Kharisma, Irdawati, S.Kep., Ns., M.Si.Med (2016)
Washing hands seem to have not be culture or habit of being applied in the real world. There are still many children are see that easy actually but they have not they apply to daily life. The children do not understand about the importance of hand washing. Parents role an important in encouraging handwashing for children. This research purpose to know the correlation between knowledge of mothers about hygiene with hand washing behavior in pre-school children in TK Karangasem Surakarta. This research is descriptive correlative with cross sectional approach. Sample in this research was all the mothers and kids school in TK Karang Indriya and in TK Rosa Indah Karangasem surakarta 60 respondents. The research instrument used questionnaire that has been tested for validity and reliability first. Data analyzed using chi square for a significant level of 95%. This reseacrh shows the results of mother's knowledge level of cleanliness, most with a high level of knowledge. While, hand washing behavior in pre school children, mostly with bad behavior. The conclusion of the research is there was a correlation between relation level of knowledge of mothers about hygiene with hand washing behavior in pre school children in TK Karangasem Surakarta (p <0.05). Keyword key : knowledge, hygiene, and handwashing, pre-school children